A novel uveitis model induced by lipopolysaccharide in zebrafish - Xiao, Xiao; Liu, Zhangluxi; Su, Guannan; Liu, Huan; Yin, Wenhui; Guan, Yuxuan; Jing, Shixiang; Du, Liping; Li, Fuzhen; Li, Na; Yang, Peizeng (Frontiers in Immunology, 2022)
Objective Endotoxin-induced uveitis (EIU) is an important tool for human uveitis study. This study was designed to develop a novel EIU model in zebrafish. Methods An EIU model in zebrafish was induced by intravitreal lipopolysaccharide (LPS) injection and was assessed dynamically. Optical coherence tomography (OCT) was used to assess infiltrating cells in the vitreous body. The histological changes wereevaluated using HE staining and immune cells were measured by immunofluorescence. The retinal RNA Sequencing (RNA-Seq) was used to explore the transcriptional changes during inflammation. RNA-Seq data were analyzed using time-course sequencing data analysis (TCseq), ClueGO plugin in Cytoscape, and Gene Set Enrichment Analysis (GSEA) software. Flow cytometry and retinal flat mounts were used to dynamically quantify the immune cells. Results EIU was successfully induced in zebrafish following intravitreal LPS injection. Inflammation appeared at 4 hours post injection (hpi), reached its peak at 24 hpi, and then resolved at 72 hpi. Immunofluorescence confirmed that massive influx ofneutrophils into the iris and vitreous body, and activation of microglia as evidenced by ameboid-shaped appearance in the retina. Retinal RNA-seq during the EIU course identified four gene clusters with distinct expression characteristics related to Toll-likereceptor signaling pathway, cytokine-cytokine receptor interaction, NOD-like receptor signaling pathway, and extracellular matrix (ECM)-receptor interaction, respectively. Prednisone immersion inhibited the inflammatory response of EIU in zebrafish, whichwas confirmed by decreased neutrophils detected in flow cytometry and retinal flat mounts. Conclusions We developed a novel EIU model in zebrafish, which may be particularly useful for gene-editing and high-throughput screening of new drugs for the prevention and treatment of uveitis.